2014
DOI: 10.1086/676438
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Surgical Site Infection in Colorectal Surgery: The Japan Nosocomial Infections Surveillance

Abstract: For colorectal operations, inclusion of additional variables routinely collected in JANIS can more accurately predict SSI risk than can the NNIS risk index alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
47
4
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 19 publications
6
47
4
3
Order By: Relevance
“…In contrast, Morikane et al (18) found an association between male sex and increased risk of SSI in adult patients undergoing colorectal surgery. The reasons for SSI being more common in female than male patients in three of these four studies is unclear; however, Pedroso-Fernandez et al (17) proposed in a personal communication that the procedure for extracting the resected tissue and size of incision may differ in female patients for cosmetic reasons.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, Morikane et al (18) found an association between male sex and increased risk of SSI in adult patients undergoing colorectal surgery. The reasons for SSI being more common in female than male patients in three of these four studies is unclear; however, Pedroso-Fernandez et al (17) proposed in a personal communication that the procedure for extracting the resected tissue and size of incision may differ in female patients for cosmetic reasons.…”
Section: Discussionmentioning
confidence: 85%
“…In adult colorectal surgery, dirty or contaminated surgery, open ileostomy or colostomy placement, emergency surgery, and multiple procedures are reportedly associated with increased risk of SSI (17,18). Segal et al (19) reported that risk factors for I-SSI and OS-SSI differ in patients who undergo colon resection.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SSI following rectal cancer surgery widely varies, ranging from 7.6% to 26.7% [10][11][12][13][14][15][16]. Such cancer surgery is technically more demanding than colonic surgery, as patients are frequently after neoadjuvant radiotherapy and that operation times are usually longer.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it therefore seems appropriate to analyse treatment outcomes separately. Many studies have found that SSI occurs more frequently in rectal cancer patients undergoing surgery than in those being operated for colonic cancer [11][12][13][14]17]. A study by Konishi et al on 556 patients after large bowel resection found that in those post-rectal resection, SSI occurred twice more frequently compared to patients who had undergone colonic resection, (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…7 The NNIS risk index was calculated on the basis of surgical wound class, operative time, American Society of Anesthesiologists (ASA) score, and endoscope use, and it has been applied in various countries such as Germany, 4,8 Australia, 9,10 Holland, 5,11,12 France, 6 Spain, 13 and Japan. 14,15 Despite its use in these countries, the NNIS risk index is associated with the following issues: (1) the use of only 4 risk factors may be inadequate for the calculation of the risk index, 11,12,14,16 (2) the calculation of each risk factor as a dichotomous variable may not be optimal, (3) the different surgery types may warrant different weights, 9,11,17 and (4) the assignment of the same weight (1 point) to each risk factor may be unjustified. 9,11 In 2009, the US National Healthcare Safety Network (NHSN) introduced statistical modeling to replace the NNIS risk index to estimate expected infection incidence, which was then used as the denominator in a new measure for investigating infections.…”
mentioning
confidence: 99%